If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3 + 6 = -23 + 5x Reorder the terms: 3 + 6 + x = -23 + 5x Combine like terms: 3 + 6 = 9 9 + x = -23 + 5x Solving 9 + x = -23 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 9 + x + -5x = -23 + 5x + -5x Combine like terms: x + -5x = -4x 9 + -4x = -23 + 5x + -5x Combine like terms: 5x + -5x = 0 9 + -4x = -23 + 0 9 + -4x = -23 Add '-9' to each side of the equation. 9 + -9 + -4x = -23 + -9 Combine like terms: 9 + -9 = 0 0 + -4x = -23 + -9 -4x = -23 + -9 Combine like terms: -23 + -9 = -32 -4x = -32 Divide each side by '-4'. x = 8 Simplifying x = 8
| 3(-6-3n)+5n=-2(-8n-1) | | -6x-7x=3x-4x | | (3x-9z)2= | | -6x-7x=3x-4c | | -4+3b+b=-3+3b | | -t^2+16t+40=0 | | (3+2a)(2a-3)= | | -12-3n=6(12n-2) | | 17+11v=8+4(-7+12v) | | -3+4r=-23-r | | 0=16t-t^2+40 | | 3x-12x=10-4x | | 4=100y^2 | | -3(1+n)+7n=5(2+n) | | 12+7-6x-7=4-7x | | 0=16-t^2+40 | | 5x-5x-1=2x+5 | | 33-3a=6(a-5) | | 8(7r-1)=-8+2r | | 8(-8+4x)=-36+4x | | 8(-8+4x)=36+4x | | 2(4-4n)=-6+6n | | 9x+13=11x | | 17x+108=y | | 8w-11=69 | | 16=-16x^2+36 | | 10=-16x^2+46 | | x/(1-x)=1.44 | | F(x)=x^100-1 | | 2m=11-3m | | r^3+3r-10=0 | | 6x^2+3x-c=0 |